Encouraging Students in Composing English Descriptive Essay through the Implementation of Growing Gardening Metaphors - Khadijah Maming; Sianna Sianna; Putri Mutiara Sari (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research was compiled from the findings of observations of writing skill in composing descriptive essay of eight grade students at MTs Negeri 2 Sidrap. Many students had low writing skill in composing descriptive essay. They cannot compose English decriptive text which is caused by learning process used does not help the students. The researcherss concludes that by using growing gardening metaphors as a learning strategy it can help students to make a good writing especially in composing descriptive essay. Therefore, the objective of this research is to find out and analyze whether the implementation of growing gardening metaphors can improved students writing skill in composing descriptive essay in the eight grade of MTs Negeri 2 Sidrap, South Sulawesi. The researcherss applied a quasi-experimental method with a two-group design. The samples of this research consists of two classes, namely the experimental class and control class. In collecting the data with pretest and posttest, the form is a writing descriptive essay test and treatment in four meetings. In data analysis, the researchers used SPSS 26 to calculate the independent sample t-test. The results of data analysis showed there is an improvement in students’ writing skill in composing descriptive essay. It is proved by the mean score of pretest is 51.94 and the mean score of posttest is 86.38. It can be concluded that teaching writing especially in composing descriptive essay by using growing gardening metaphors as a learning strategy can encourage the students in composing English descriptive essay. As a result, it potentially promote the students’ writing skill.